FACTORS AFFECTING WORKERS’ SATISFACTION WITH HUMAN RESOURCE MANAGEMENT AT HAI PHAT REAL ESTATE JOINT STOCK COMPANY, HANOI - Van Hoa, Ho; Thanh Que, Pham; Huyen Phuong, Pham; Thi Hai, Nguyen; Thu Ha, Tran (Journal of Forestry Science and Technology, 2020)
The study is based on the survey data on 250 officials and employees of Hai Phat Real Estate Joint Stock Company, using the Exploratory Factor Analysis (EFA) method to identify the satisfaction level and the factors affecting employee satisfaction with human resource management at Hai Phat Real Estate Joint Stock Company. The research results indicate that the employees evaluate the Company’s human resource management at a relatively good level and there are 5 groups of factors with 24 elements affecting human resource management in the Company. In which: the biggest impact is salary, bonus and welfare (β = 0.235), the second is the working environment (β = 0.240), the third is Promotion opportunity (β = 0.186), the fourth is the recruitment process (β = 0.177) and finally it’s the Job characteristics (β = 0.140). From these results, the research proposes a number of solutions to improve the human resource management at Hai Phat Real Estate Joint Stock Company including: improve remuneration and remuneration policies for employees; improve the working environment to ensure workers are friendly and the best conditions; There are specific criteria to ensure favorable conditions for employees to have the opportunity to develop capacity and advance; improve the qualifications of the team right from the beginning, the recruitment process should combine training from where, recruitment information should be detailed and clear.